35 The impact of cardiovascular disease on sex-specific adverse outcomes following intact abdominal aortic aneurysm repair: a systematic review, meta-analysis & meta-regression. (4th June 2021) - Pouncey, Anna Louise; David, Michael; Morris, Rachael; Ulug, Pinar; Martin, Guy; Bicknell, Colin; Powell, Janet
Abstract : Introduction: Cardiovascular disease is a major cause of death in men with an AAA. Women experience higher operative mortality than men for open (OAR) and endovascular (EVAR) repair of intact abdominal aortic aneurysm (AAA), but the reason for this is not yet established. This study aimed to define differences in cardiovascular pre-operative co-morbidity and peri/post-operative complications for men and women under-going OAR and EVAR, to explore the impact of cardiovascular disease on adverse outcomes following intact AAA repair. Methods: A systematic review, meta-analysis and meta-regression of sex-specific differences in mortality and complications was conducted and reported according to PRISMA and Cochrane guidance, and registered with Prospero (CRD42020176398). Papers reporting outcomes for men and women, following intact primary AAA repair, from 2000-2020 world-wide were included. Separate analyses were conducted for EVAR and OAR. Data sources included: Medline, Embase and CENTRAL databases 2005-2020 searched using ProQuest Dialog™. Results: A total of 26 studies (371, 215 men, 65, 465 women) were included. Risk of 30-day mortality was higher in women for OAR and more so for EVAR (OR [95%CI] 1.49 [1.37, 1.61] and 1.86 [1.59, 2.17] respectively), and remained following multivariate risk factor adjustment. Although assessment of pre-operative co-morbidities was limited by heterogeneity, cardiac disease was more commonly diagnosed in men (OAR OR 0.72 [0.59, 0.88]; EVAR OR 0.65 [0.48, 0.87]) no differences in peripheral vascular disease or smoking history were observed. However, following OAR, the likelihood of acute coronary complications was similar for both sexes (OR 1.18 [0.98-1.42]) and following EVAR, for women, the likelihood of acute coronary complication was significantly higher (OR 1.19 [1.03, 1.37]). Renal injury, arterial injury and limb ischemia were also more common in women undergoing EVAR (ORs 1.46 [1.22-1.72], 3.02 [1.62-5.65], 2.13 [1.48-3.06] respectively) ( figure 1 ). Meta-regression revealed cardiac complications were significantly associated with greater mortality risk differential between men and women ( Figure 2 ); the association of renal complications with death was of borderline significance. Conclusions: The excess risk of 30-day mortality for women following AAA repair has not abated with time, with an increased risk differential for EVAR over OAR. Although our meta-analysis identified a lower prevalence in pre-operative diagnosis of coronary artery disease amongst women, acute coronary complications were significantly higher for women following EVAR, and similar to men following OAR. An increase in acute coronary complications for women compared to men was associated with a higher mortality risk differential. Women were also at greater risk of additional arterial complications leading to renal injury and limb ischaemia. These findings suggest that cardiovascular disease has significant impact on adverse outcomes for women after AAA repair. Further work to improve identification and treatment of cardiovascular disease in women is needed and has the potential to address disparity in outcomes for AAA repair. Figure 1 . Comparison of 30-day complications for men and women following (a) OAR and (b) EVAR. Figure 2 . (a) Meta-regression of log odds of (a) cardiac complications and (b) renal complications against log odds of 30-day/in-hospital mortality for women (vs. men) following endovascular repair of AAA (EVAR). (Cardiac: n= 8, βi =2.96 (se =1.27), p=0.02, tau2 = 0.00; renal: n=8, βi =2.50 (se =1.31), p=0.056, tau2 = 0.01). Conflict of Interest: None